Harnessing Vehicle-to-Pedestrian (V2P) Communication Technology: Sending Traffic Warnings to Texting Pedestrians - Rahimian, Pooya; O’Neal, Elizabeth E.; Zhou, Shiwen; Plumert, Jodie M.; Kearney, Joseph K. (Human factors, 2018)
Objective: We examined how sending mobile-device warnings to texting pedestrians when they initiate an unsafe road crossing influences their decisions and actions. Background: Pedestrian texting has been identified as a key risk factor in pedestrian–vehicle collisions. Advances in sensing and communications technology offer the possibility of providing pedestrians with information about traffic conditions to assist them in safely crossing traffic-filled roadways. However, it is unclear how this information can be most effectively communicated to pedestrians. Method: We examined how texting and nontexting pedestrians crossed roads with continuous traffic in a large-screen, immersive pedestrian simulator using a between-subjects design with three conditions: texting, warning, and control. Texting participants in the warning condition received an alarm on their cell phone when they began to cross a dangerously small gap. Results: The results demonstrate the detrimental influence of texting on pedestrians’ gap selection, movement timing, and gaze behavior, and show the potential of warnings to improve decision making and safety. However, the results also reveal the limits of warning texting participants once they initiate a crossing and possible overreliance on technology that may lead to reduced situation awareness. Conclusion: Mobile devices and short-range communication technologies offer enormous potential to assist pedestrians, but further study is needed to better understand how to provide useful information in a timely manner. Application: The technology for communicating traffic information to pedestrians via mobile devices is on the horizon. Research on how such information influences all aspects of pedestrian behavior is critical to developing effective solutions.